Factors influencing the uptake of public health interventions delivery by community pharmacists: A systematic review of global evidence - Mumbi, A; Mugo, P; Barasa, E; Abiiro, GA; Nzinga, J (Public Library of Science, 2024)
Background: Community pharmacies are the first point of contact for most people seeking treatment for minor illnesses globally. In recent years, the role of community pharmacists has evolved, and they play a significant role in the delivery of public health interventions (PHIs) aimed at health promotion and prevention such as smoking cessation services, weight management services, HIV prevention, and vaccination. This review aims to explore the evidence on the factors that influence community pharmacists to take up the role of delivery of such interventions. Methods: Three electronic databases namely, Embase (1947-December 2023), Medline (1975-December 2023), and Scopus (1823-December 2023) were searched for relevant literature from the inception of the database to December 2023. Reference lists of included articles were also searched for relevant articles. A total of 22 articles were included in the review based on our inclusion and exclusion criteria. The data were analyzed and synthesized using a thematic approach to identify the factors that influence the community pharmacist’s decision to take up the role of PHI delivery. Reporting of the findings was done according to the PRISMA checklist. Findings: The search identified 10,927 articles of which 22 were included in the review. The main factors that drive the delivery of PHIs by community pharmacists were identified as; training and continuous education, remuneration and collaboration with other healthcare professionals. Other factors included structural and workflow adjustments and support from the government and regulatory bodies. Conclusions: Evidence from this review indicates that the decision to expand the scope of practice of community pharmacists is influenced by various factors. Incorporating these factors into the design of policies and public health programs is critical for the successful integration of community pharmacists in the delivery of broader public health to meet the rising demand for health care across health systems.